PENGARUH PEMBERIAN PUDING TOMAT DAN WORTEL TERHADAP KADAR KOLESTEROL TOTAL PASIEN HIPERKOLESTEROLEMIA DI RSI SITI KHADIJAH KOTA PALEMBANG - Eliza - Sutarman; Dinda Syafitri; Sartono Sartono; Sumarman Sumarman (POLTEKKES KEMENKES MANADO, 2020)
Hypercholesterolemia was a condition where the occurrence of fat metabolism disorders is characterized by an increase in total cholesterol levels in the blood that exceeds normal levels. High cholesterol levels will cause blockages in blood vessels and disrupt circulation of the circulatory system. One non-pharmacological therapy that can help reduce cholesterol levels is the provision of tomato and carrots pudding. Tomatoes and carrots are plants that contain antioxidants including carotenoids, vitamin C, vitamin E and lycopene and fiber which are good for reducing total cholesterol in the blood. This study aim to determine the effect of giving tomato and carrot pudding in reducing total cholesterol levels in outpatient hypercholesterolemia patients at Siti Khadijah Hospital, Palembang City. The method used in this study was a quasi-experimental study with a pre-test and post-test with control group design. The sample in this study was taken by purposive sampling with a total sample of treatment and control groups of 30 people each. Provision of tomato and carrot pudding is done for 7 days. Data analysis uses paired sample t-test and independent sample t-test. The Results of research showed an average difference in total cholesterol levels in the treatment group of 40.9 mg / dl (p-value = 0,000) and in the control group of 21.36 mg / dl (p-value = 0,000). Statistical test results (independent t-test) obtained p value <0.05 (0.001). The Conclusion from this study was tomato and carrot pudding have a significant effect in reducing total cholesterol levels in hypercholesterolemia patients.